Gambaran Penggunaan Sistem Informasi Manajemen Puskesmas (Simpus) dengan Metode Utaut di Puskesmas Daerah Jakarta Utara - Darmawan, Risma; Harahap, Sarah Geltri; Ludovikus, Ludovikus (Universitas Malahayati, 2024)
ABSTRACT The health center management information system is data that is managed into data and has useful value aimed at increasing knowledge in supporting health development. The theory used is the UTAUT theory (Unified Theory of Acceptance and Use of Technology) which is a development theory of the TAM (Technology Acceptance Model) , in the UTAUT theory there are 4 indicators of Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions. Descriptive method, quantitative approach. The instrument used was a questionnaire with 121 respondents. The population in this study were all health workers at community health centers that used SIMPUS. The results of data analysis with the highest percentage in the good category are Performance Expectancy of 95.9%. In the Effort Expectancy indicator, some respondents felt that their expectations were met as much as 94.2%. In the Social Influence indicator, 84.3% of respondents felt influenced. In the Faciliating Conditions indicator, some respondents felt sufficiently supported by the facilities provided by the agency, 85.1%. It can be stated that the highest percentage of use of SIMPUS with the UTAUT method is Performance Expectancy where the indicator with SIMPUS really helps officers in operational activities. Keywords: Management Information Systems, Knowledge, Community Health Center, UTAUT ABSTRAK Sistem informasi manajemen puskesmas suatu data yang dikelola menjadi data dan memiliki nilai guna bertujuan sebagai bahan meningkatkan pengetahuan dalam mendukung pembangunan kesehatan.Teori yang digunakan yaitu teori UTAUT (Unified Theory of Acceptance and Use of Technology) merupakan teori perkembangan dari TAM (Technology Acceptance Model),pada teori UTAUT ada 4 indikator Perfomance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions. Metode deskriptif pendekatan kuantitatif. Instrumen yang digunakan yaitu kuesioner atau angket dengan 121 responden. Populasi pada penelitian ini yaitu seluruh petugas kesehatan di puskesmas yang menggunakan SIMPUS. Hasil analisis data dengan persentase tertinggi dalam kategori baik yaitu Perfomance Expectancy sebanyak 95,9%. Pada indikator Effort Expectancy sebagian responden merasa harapannya terpenuhi sebanyak 94,2%. Pada indikaror Social Influence sebagian responden merasa terpengaruh sebanyak 84,3%. Pada indikator Faciliating Conditions sebagian responden merasa cukup di dukung dengan adanya fasilitas yang telah disediakan oleh pihak instansi sebanyak 85,1%. Dapat di nyatakan bahwa penggunaan SIMPUS dengan metode UTAUT persentase tertinggi dimiliki oleh Perfomance Expectancy dimana pada indikator dengan adanya SIMPUS sangat membantu petugas dalam kegiatan operasional. Kata Kunci: Sistem Informasi Manajemen, Pengetahuan,Puskesmas,UTAUT